Early Mistreatment Contributes to Social Behavior Disorders in Zebrafish - Menezes, Fabiano Peres; Padilha de Sousa, Igo; Luchiari, Ana Carolina (Frontiers in Behavioral Neuroscience, 2020)
Adverse experiences during childhood have been the focus of a series of studies due to the psychological damage observed in individuals who suffered abuse during their youth. Studies with model animals that can mimic these observations can significantly contribute to understanding the mechanisms behind this phenomenon. In our experiments, young zebrafish (20dpf) were exposed to aggressive alcoholized male adults for 30 min for 10 days. At 30 dpf the animals were tested for shoal formation and at 60 dpf, locomotion and aggression were evaluated. Animals that suffered oppression from adults showed greater group cohesion, and lower attack emission and higher distance from the image in the mirror test. Locomotor parameters were not changed. These results show that the stress caused by aggression exposure in the juvenile phase led to increased fear and avoidance behavior later in life. Moreover, we confirm the importance of the zebrafish as a sensitive tool for studies on the effects of early mistreatment and its consequences to adult behavior.